(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Haemophogocyticlymphohistiocytosis (HLH) is a rare but potentially fatal disease, which describes a clinical syndrome of hyper-inflammation resulting in uncontrolled and ineffective immune response. It appears commonly in infancy, although it has been seen in all age groups. A vast majority of cases are acquired due to secondary causes (infections, autoimmune, malignancy, metabolic disorders) but primary HLH (genetic) is also not uncommon which also gets triggered by infection as suggested by recent studies. “Hypercytokinemia” which is the hallmark of HLH can result in end organ damage and even death in some cases if there is delay in diagnosis. The pathological hallmark of this syndrome is uncontrolled activation of T lymphocytes and macrophages, together with an impaired cytotoxic function of NK cells and CD8+T lymphocytes resulting into massive cytokine release (e.g. interferon-ã, TNF-á, Interleukin-6, 8, 10, 12, 18) from this cells and overwhelming inflammation. Lymphocytes and macrophages sometimes with haemophagocytic activity accumulate in bone marrow, spleen, liver or lymph nodes. This disorder is characterized by fever, hepatosplenomegaly, lymphadenopathy, skin rash, cytopenias, hepatitis, coagulopathy, and neurological symptoms. We report a case of 55 yr. old male presenting with fever and high colored urine who developed clinical and laboratory findings consistent with diagnosis of HLH according to HLH-2004 guidelines. Unfortunately the patient died despite receiving chemotherapy. HLH has multifaceted clinical presentations with often non-specific signs and symptoms that are often found in other clinical conditions. Early recognition of HLH is critical in initiating therapy early and preventing high mortality resulting from multi-organ failure. J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 51-58